2009
DOI: 10.1186/1742-4690-6-54
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-infection and recombination in HIV-1 within a longitudinal cohort of women

Abstract: Background: Recombination between strains of HIV-1 only occurs in individuals with multiple infections, and the incidence of recombinant forms implies that multiple infection is common. Most direct studies indicate that multiple infection is rare. We determined the rate of multiple infection in a longitudinal study of 58 HIV-1 positive participants from The Women's Interagency HIV Study with a richer sampling design than previous direct studies, and we investigated the role of recombination and sampling design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
(65 reference statements)
3
37
0
Order By: Relevance
“…We sequenced 30 viruses from each of the Thai individuals having B-clade infections and found no traces of CRF01 coinfection; however, CRF01 may have been present at levels too low to detect by this method. Also, transiently detected superinfections have been reported (97,98). Alternatively, host factors, whether genetic or environmental (e.g., exposure to an HIV-1 cross-reactive epitope from an organism in the Thai communities where the samples were obtained), might explain the shared serological profiles (84).…”
Section: Discussionmentioning
confidence: 99%
“…We sequenced 30 viruses from each of the Thai individuals having B-clade infections and found no traces of CRF01 coinfection; however, CRF01 may have been present at levels too low to detect by this method. Also, transiently detected superinfections have been reported (97,98). Alternatively, host factors, whether genetic or environmental (e.g., exposure to an HIV-1 cross-reactive epitope from an organism in the Thai communities where the samples were obtained), might explain the shared serological profiles (84).…”
Section: Discussionmentioning
confidence: 99%
“…1 This analysis examined the protease-RT region of pol and the C2V5 region of env amplified from two to four samples from 58 women at 6-to 24-month intervals, and showed findings similar to the present study with regard to temporal fluctuation of the dually infecting strains, in that of the 18 cases in which dual infection was identified at a single interim time point, 16 found no evidence of the second strain in subsequent samples, and in three cases, the initial strain was almost overtaken by the second strain. Furthermore, it was found that among the 31% who were dually infected, recombination had occurred between the pol and env loci in nearly all individuals, and recombination within the loci studied had occurred in three individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Among such studies includes one published by Baird et al, which examined the C1C4 region of env for recombination between two discordant HIV-1 subtypes, A and D, in cell culture demonstrating an abundance of recombinants and revealing recombination breakpoints occurring more frequently in the constant than in the variable regions of the viral envelope. 8 Subsequent in vitro studies with these discordant strains also revealed that factors such as replicative fitness contribute to the frequency at which two viral strains recombine.…”
mentioning
confidence: 99%
“…Pol sequencing alone, which is easily available as part of the routine testing for drug resistance mutations of treated patients, can be used as a second tool to screen for HIV-1 superinfection, which might be associated with consequent changes in the pol sequence and/or treatment susceptibility [60]. Nevertheless, HIV-1 superinfections are more frequently detected when two distinct regions of the viral genome rather than one are sequenced, and samples from different time points analyzed [52,54,62]. Finally, a major drawback of population-based sequencing is its lack of sensitivity to detect strains that are underrepresented in the quasi species population, and alternative methods, such as heteroduplex mobility assay and ultra-deep sequencing, might be more appropriate to detect superinfections [63][64][65].…”
Section: What Is the Incidence Of Hiv-1 Superinfection?mentioning
confidence: 99%
“…However, despite the flourishing literature on the subject, there is a current lack of technology and available data to clearly determine the incidence of this phenomenon. Cross-sectional studies [51] or longitudinal follow-ups with limited sampling over time [52] might not represent adequate settings to assess superinfection incidence rates. Combined with a lack of adequately sensitive techniques to reliably identify this event, the true prevalence of superinfection is likely to be underestimated and still subject to intense controversy (reviewed in [53]).…”
Section: What Is the Incidence Of Hiv-1 Superinfection?mentioning
confidence: 99%